Use of Probiotics for Safe Quail Meat Production - Prodip Kumar Sarkar; Dip Majumder Ridoy; Mehedi Islam Moon; Swapon Kumar Fouzder (Turkish Journal of Agriculture: Food Science and Technology)
Safe meat production is an important aspect to avoid human health hazards. The use of probiotics in poultry is an important tool to produce safe meat among several established biotechnological approaches. In this experiment, we studied the effects of probiotics for producing safe Japanese quail meat. 150 Japanese quail chicks were reared for a period of six weeks using various doses of probiotics (0, 0.5, 1, 1.5, and 2g per litre of water). The chicks were randomly distributed into five treatment groups with three replications each. The number of birds in each replication was 10. After rearing six weeks, significantly high body weight was found at probiotic concentrations of 1, 1.5, and 2g per litre of water. The feed intake in various treatments did not differ significantly, but comparatively better feed conversion ratios were observed at probiotic treatments. Water quality was not significantly differed as a result of addition of probiotics to the water. The reason for this better growth performance is probably due to the multiple benefits of probiotics in poultry. Probiotics could have maintained gut health with better nutrient utilization and availability that might have been led to higher body weight gain in the quail. In future experiments, challenging the birds with diseases or comparing probiotics with antibiotic growth promoters is required to ensure the efficiency of probiotics.